MALES’ ATTITUDES TOWARDS SELF-REALIZATION IN PATERNITY - Navaitis, Gediminas (Acta Paedagogica Vilnensia, 2007)
The article deals with Lithuanian males’ attitudes towards self-realization in paternity. The research data was collected by standardized interview method, and 1376 males were interviewed as well.The results of this research revealed the fact that majority (77,1%) of participants, when describing the husband’s role, were speaking about care and provision for family. It means, that in most cases were picked out the financial and instrumental aspects of masculinity. Paternity was evaluated as high: 84,1% of participants had the positive attitude towards their paternity and had the opinion that they do correspond to the father’s characteristics, 7,3% – do not.Such distribution of answers let us to conclude that majority of participants perceive the demands of husband’s role as greater than of father’s role.Participants described the father’s role through children care and maintenance in that way marking out  the instrumental and financial aspect of father’s role. The role of father as the spiritual leader, giving the examples of courage, honor and strength was perceived little. And the role of father in the baby development was perceived little too.Overall, the results of the research disclose the male’s self-realization problem in our society as well as their attitudes towards paternity.
Keywords: paternity; self-realization; attitudes; father’s role; standardized interview